Resolubility of eye care in a secondary care center: a quantitative approach - Regina Mainini Oliveira, Ines Paula [UNESP]; Meneguin, Silmara [UNESP] (Inst Israelita Ensino & Pesquisa Albert Einstein, 2019)
Objective: To evaluate the resolubility of ophthalmologic care in an integrated health center. Methods: This was a cross-sectional study including 816 patients who were attended from November 2013 to November of 2015. Data were collected from a medical consultation database and patients' medical records. Results: The majority of participants were women, non-diabetic, and had high school education. The main cause of referral for ophthalmologic evaluation was the consultation with a specialist, the waiting time for consultation was shorter for non-diabetic patients. Conclusion: This Integrated health center presented, partial resolubility conditions to meet the ophthalmologic needs of users of the Brazilian Unified Health System. Eye care needs to be reorganized particularly by consider the priority cases of those at ophthalmological risk, and referrals should be done to the adequate care level and on time to guarantee resolubility.
Keywords: Unified Health System; Diabetes mellitus; Secondary care; Eye health